Effect of quercetin and avobenzone concentration on physical characteristics and in vitro activity of sunscreen - Wisudyaningsih, Budipratiwi; Barikah, Kuni Zu’aimah; Lita, Fernanda Indah (Fakultas Farmasi Universitas Andalas, 2023)
Quercetin is a flavonoid compound that has great potential activity, one of which is a chemical absorber of ultraviolet (UV) radiation, especially UV B radiation. The objective of the present study was to optimize quercetin as a UV B absorber combined with avobenzone as a UV A absorber in sunscreen cream formulation. Optimization was carried out by factorial design method using Design Expert 11.0 Software, with viscosity, pH, Sun Protection Factor (SPF) value, Percent of Erythema Transmission (% TE), and Percent of Pigmentation Transmission (% TP). The results showed that the quercetin factor was decreasing viscosity, pH, % TE, and % TP value but increasing the SPF value of the formulation. Avobenzone factor affected the increase of viscosity, pH, and SPF value but decreased the % TE and TP value. The interaction of quercetin and avobenzone significantly affected decreasing the viscosity and pH value but increased the SPF < % TE, and % TP value. Evaluation of optimum formula obtained by the overlay contour plot on the software resulting viscosity cream at 338,33 dPas, pH value at 5,40; SPF value at 33,31; % TE at 2,62x10-3 % and % TP at 1,56x10-5 %.